Use of discourse linkers in academic journals : an analysis of native and non-native writers - Ahmad Fuad bin Mohd Paiz (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Discourse Linkers (DLs) are included into academic texts to ensure smooth information flow. Academic writing, unlike other genres, is complex and requires substantial amount of DLs to be used as sign posting devices. Writers must have a good understanding on the specific functions in order to apply them correctly. This study was carried out to compare the patterns of DLs' use between international and Malaysian writers. The main objectives of this study were to observe the frequency of DLs' and range of DLs use. To observe such patterns, 40 international and Malaysian academic journals articles were collected from online databases. Liu's (2008) design provided the framework the study, with additional functions and tokens taken from two other researchers. The design included the study of 13 functions: additive/emphatic, reformulation, similarity/comparative, particularizing, adversative/concessive, contrastive, correction, resumptive, causal/resultative, conditional causal, enumerative/listing, summative/closure, and simultaneous. The study revealed that Malaysian and international writers were using DLs somewhat differently even though statistical analysis indicates the differences are not significant. Overall, Malaysian writers included DLs more frequently than international writers; and also, they used more causal/resultative linkers. But in term of range, international writers have larger sets of tokens than Malaysian writers. Further inspections on texts also reveal that both groups have distinctive approaches in incorporating DLs in academic texts. The findings of this research are valuable for postgraduates and researchers as the awareness created may be useful in shaping journal writing.